Controle epigenético do elemento de transposição mariner em populações de Drosophila melanogaster - Stoffel, Tailini Jordana Reinehr (2016)
One of transposons families most well-known is the mariner family. mariner is not found in natural populations of Drosophila melanogaster, however, white-peach mariner and Mos1 were introduced in this species by genetic transformation. In the last decade, significant advances have been made in the understanding the epigenetic control of transposable elements. The major regulators in Drosophila TEs are piRNAs from piRNA clusters. These can suppress TEs either by post transcriptional gene silencing, from the cleavage of transcripts of an TE, as by transcriptional silencing of genes through changes in chromatin. Therefore, this dissertation aimed to investigate the existence of epigenetic white gene inactivation in D. melanogaster mediated by mariner element presence in the white-peach line. To assess the activity of the mariner element in natural populations of D. melanogaster were made isofemale strains. For analysis of gene inactivation of white phenotypic tests were performed by experimental crosses. One white eye strain with inactive white gene, but with active mariner, also been established. In order to verify the gene expression in different white lines of D. melanogaster, and to detect the presence of mariner element into the genome of D. melanogaster, isofemale strains were quantified by RT-qPCR. In silico searches for mariner in a piRNAs database and following the piRNA flamenco cluster were carried out to check if there is a cluster of piRNA for mariner in D. melanogaster. mariner had a very high expression in populations of D. melanogaster analyzed. Furthermore, phenotypic testing point to the white-mediated gene inactivation the presence of mariner through heterochromatin formation because the F2 breeding carried out showed flies with wild eye, peach until pure white. These data corroborate the results found by RT-qPCR. It found no similar sequence in the mariner piRNA database and Flamenco or in sequence, however, the existence of a cluster piRNA still can not be excluded as new clusters can still be discovered. The copy number mariner was very variable between the lineage of individuals with active and inactive mariner white gene, ranging from 3 to 15 copies per individual, which was expected by the fact that this line was established shortly.